Age differences in change-of-direction performance and its subelements in female football players - Hirose, N.; Nakahori, C. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To describe cross-sectional age differences in change-of-direction performance (CODp) in female football players and investigate the relationship between CODp and linear-sprint speed, muscle power, and body size. Methods: A sample of 135 well-trained female football players was divided into 8 age groups. Anthropometry (height, body mass, and lean body mass) and athletic performance (10-m sprint speed, 10-m × 5-CODp, and 5-step bounding distance) were compared to determine interage differences using ANOVA. Then, the participants were divided into 3 age groups: 12- to 14-y-olds, 15- to 17-y-olds, and =18 y-olds. Simple- and multiple-regression analyses were conducted to determine the correlation between CODp and the other measurement variables in each age group. Results: Age-related differences were found for CODp (F = 10.41, P < .01), sprint speed (F = 3.27, P < .01), and bounding distance (F = 4.20, P < .01). Post hoc analysis revealed that the CODp of 17-y-old players was faster than that of 16-y-old players (P < .01), with no interage differences in sprint speed and bounding distance. Sprint speed and bounding distance were weakly correlated with CODp in 15- to =18-y-old players, but only sprint speed was correlated with CODp in 12- to 14-y-old players. Conclusions: CODp improves from 16 to 17 y of age in female players. Linear-sprint speed, muscle power, and body size were weakly correlated with the age differences in CODp.